Limited transferability of human capital across countries - the case of workers with foreign qualifications in Germany - Daniela Rohrbach-Schmidt; Michael Tiemann (Bundesinstitut für Berufsbildung (BIBB), 2016)
So far, only limited evidence exists on skill utilisation beyond over- or under-education among immigrants. Our study tries to fill this gap by exploiting recent data of the BIBB/BAuA Employment Survey 2012, which allow for observing levels of both educational and skill mismatch among workers with foreign qualifications. For this, we focus on a sample of immigrant workers that is comparatively highly qualified, and thus respresents a selective sample of the much larger group of all migrants in Germany. The results of a propensity-score based reweighting approach suggest that, even in this selective group, being an immigrant significantly increases the probability of being over-educated, but that some part of the educational mismatch can be attributed to skills heterogeneity. (Authors' abstract, BIBB-Doku) – – Bisher liegen keine Arbeiten zur Ausnuẗzung von fachlichen Kenntnissen und Faḧigkeiten im Zusammenhang mit formaler Fehlqualifizierung bei erwerbstaẗigen Immigranten in Deutschland vor. Die Studie schließt diese Forschungsluc̈ke mit Daten der BIBB/BAuA Erwerbstaẗigenbefragung 2012, welche Angaben zur Passung der Qualifikationen als auch der fachlichen Kenntnisse und Faḧigkeiten enthal̈t. Hiermit wird auf eine Stichprobe von Immigranten fokussiert, die vergleichsweise hochqualifiziert und als Kernerwerbstaẗige bereits in den Arbeitsmarkt integriert sind. Die Ergebnisse eines reweighting regression Ansatzes zeigen, dass fur̈ diese selektive Gruppe von Immigranten eine signifikant hoḧere Wahrscheinlichkeit besteht, formal ub̈erqualifiziert zu sein und keine Erwerbstaẗigkeit gemas̈s der fachlichen Kenntnisse auszuub̈en. (Autorenreferat, BIBB-Doku)
urn:nbn:de:0035-0599-6
Keywords: 370